Exploring the push-pull factors influencing parenting efficacy of fathers of children with ASD: a fuzzy set qualitative comparative analysis - Zhu, Linli; Ge, Xinbin; Huang, Weijun; Shao, Leyi; Ma, Xiaolan (Frontiers in Psychiatry, 2024)
Objectives: This study aimed to explore the core factors and configurations influencing parenting efficacy for fathers of children with ASD in Western China by using a configuration analysis.Background: Understanding the push-pull factors related to parenting efficacy for fathers raising children with ASD can support the fathers of children with ASD to participate in education affairs and improve the quality of family education, which is of significant importance to both individuals and society. This study recruited 156 fathers of children with ASD from Guangxi, China.The results suggested that there was more than one (sub) configuration for achieving a high level of parenting efficacy among fathers of children with ASD. (b) The configurations could be summarized into three main types as follows: "working within the system*flexible working time," "high level of education*high level of other support," and "severe disability*fewer interaction with wife." (c) The two variables, "family income" and "community support," were not as important as they were shown in previous studies, and their effects often depended on how they interact with other variables.Conclusions: Findings highlighted the validity of deploying configuration analysis (based on the ecosystem theory) to establish the relationship between independent variables and the parenting efficacy of fathers of children with ASD. The discovery of more than one configuration led to a new consensus on how multiple factors influence parenting efficacy. Implications were suggested for practitioners, policymakers, and future research alike.